2016
DOI: 10.1021/acs.langmuir.6b00382
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Detection Using Nematic Liquid Crystal Droplets on Anisotropic Surfaces

Abstract: Nematic liquid crystals (NLCs) form helical macroscopic structures through chiral induction when doped with chiral species. We describe a very simple, though highly sensitive method for determination of handedness and pitch of the induced twist in the case of very weak twisting powers of such chiral dopants. A tiny drop-typically less than 10 nL-of the chiral doped NLC is placed on a plate promoting a uniform planar surface anchoring of the liquid crystal director. At the curved NLC-air interface the anchoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A recent report shows achiral 5CB can form helical chiral phase when doped with a trace amount chiral molecule. [71] In our study, C153 is a chiral molecule and its presence may help 5CB and 8CB for adopting chiral phase. Due to the asymmetric packing, a finite angle is maintained between two adjacent layers of LC molecules, giving rise to a long range chirality.…”
Section: Study Of Rotational Anisotropy Decay Of C153 In Lcsmentioning
confidence: 77%
See 1 more Smart Citation
“…A recent report shows achiral 5CB can form helical chiral phase when doped with a trace amount chiral molecule. [71] In our study, C153 is a chiral molecule and its presence may help 5CB and 8CB for adopting chiral phase. Due to the asymmetric packing, a finite angle is maintained between two adjacent layers of LC molecules, giving rise to a long range chirality.…”
Section: Study Of Rotational Anisotropy Decay Of C153 In Lcsmentioning
confidence: 77%
“…However, 5CB and 8CB are achiral molecules and therefore formation of chiral nematic phase is not likely to happen here. A recent report shows achiral 5CB can form helical chiral phase when doped with a trace amount chiral molecule . In our study, C153 is a chiral molecule and its presence may help 5CB and 8CB for adopting chiral phase.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that chiral dopants generate strong helicity in the nematic phase, and the strength of a dopant to generate a helical structure is called helical twisting power (HTP). Rudquist et al [63] found that 5CB molecules formed a helical structure when doped with chiral mandelic acid with hydroxy. Kishikawa et al [64] found that the substituents of a series of chiral succinimide derivative significantly affected the formation of a helical structure of 5CB, and the derivative with a terminal hydroxyl resulted in a larger HTP than the derivative with a terminal alkyl.…”
Section: Effect Of Polarity On Molecular Orientationmentioning
confidence: 99%